2020
DOI: 10.15415/jce.2020.71003
|View full text |Cite
|
Sign up to set email alerts
|

Green Synthesis and Characterization of Silver NPs Using Oyster Mushroom Extract For Antibacterial Efficacy

Abstract: The present study was aimed to synthesize silver nanoparticles (AgNPs)using the extract of oyster mushroom Pleurotuscitrinopileatus and its use in antibacterial testing. This green synthesis approach of silver NPs is very fast, simple, environmentally friendly and economical. The initial confirmation of silver NPs synthesis was observed with the alteration of the colour of the solution from colourless to wine red. The prepared nano-material was further characterized by UV-Visible spectrophotometer, and transmi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 24 publications
1
7
0
Order By: Relevance
“…In a separate study, Kim et al 43 documented AgNPs to form pits within the cell membrane, thereby increasing cell permeability. Another study reported antibacterial potential of AgNPs synthesized using a mushroom ( Pleurotus sajor-caju ) extract, but the surface moiety was not determined in the study 44 . Research also indicates Ag + ions could inhibit bacterial growth by disrupting DNA replication and inactivating thiol groups in many enzymes 43 .…”
Section: Resultsmentioning
confidence: 97%
“…In a separate study, Kim et al 43 documented AgNPs to form pits within the cell membrane, thereby increasing cell permeability. Another study reported antibacterial potential of AgNPs synthesized using a mushroom ( Pleurotus sajor-caju ) extract, but the surface moiety was not determined in the study 44 . Research also indicates Ag + ions could inhibit bacterial growth by disrupting DNA replication and inactivating thiol groups in many enzymes 43 .…”
Section: Resultsmentioning
confidence: 97%
“…For the synthesis of NPs, the M. gigantea basidiocarps were oven dried at 40 • C for 2 hours after being rinsed with doubledistilled water. 50mL of hot, boiled, distilled water was added to 6g of powder and allowed to cool at room temperature before being filtered using Whatman-4 filter paper and employed as mushroom extract (15).…”
Section: Preparation Of Mushroom Extractmentioning
confidence: 99%
“…AgNPs are known for their high surface-to-volume ratio as well as antimicrobial and antifungal activities agents in the health sector and cosmetic industry due to their unique morphology and small size in the range from 1 to 100 nm [8][9][10]. Ongoing efforts are being made to investigate the anti-bacterial properties of AgNPs [11]. Microscopic organisms like bacteria, viruses, yeasts, and molds are often the cause of infections in human beings in their living environments.…”
Section: Introductionmentioning
confidence: 99%
“…Among these, phenol contains antioxidant [22] and antibacterial [23] compounds and plays the dual role of reducing the ions in Ag and acting as a capping agent of AgNPs surface [24]. More specifically, the mushroom extract has been used for the mycosynthesis of AgNPs because of their antimicrobial activity against pathogenic bacteria due to their critical function in destroying the bacteria's DNA and cellular macromolecules [11,19,25].…”
Section: Introductionmentioning
confidence: 99%